PKM STRATEGI PEMASARAN PRODUK UMKM RUJAK JAMBU KRISTAL DI DESA TANI BHAKTI SAMBOJA BARAT KUTAI KARTANEGARA - Dwi Taufik Rohman; Elvina Avriani; Celvin Adi Prastya; Raihana Nur Alifah; Eisa Faikhatul Hanni; Anggara Era Saputra (Jurnal Abdimas Bina Bangsa, 2023)
The marketing strategy of developing UMKM Rujak Jambu in the Desa Tani Bhakti as a village tourism which is Lamin Etam Ambors located, it turns out of having some limitation since they less of understanding about product promotion. The problem about it are caused since businessperson have not realized about the importance of marketing in any different social media, making a good photo product, and do a promotion who can make buyer be interested to buy Rujak Jambu Kristal. This kind of article used descriptive-qualitative by observation and interview with Rujak Jambu Kristal businessperson. The results of this article showed us the satisfaction of businessperson UMKM Rujak Jambu Kristal through presentation about marketing strategy on their business. The best marketing strategy of developing UMKM Rujak Jambu Kristal can improve economic of Desa Tani Bhakti, to cut off percentage of unemployment, and give a profitable things to them